MENINGKATKAN EFEKTIVITAS STRATEGI PEMBELAJARAN PAIKEM TERHADAP NILAI UJIAN AKHIR SEKOLAH - Mulyadi, Mulyadi; Suprayekti, Suprayekti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
The purpose of this study is to obtain information on the relationship between PAIKEM intsructional strategy and the school final examination of international standard (UASBN) in SD Islam Al-Azhar 20 Jakarta. This descriptive research conducted from April through July 2011 employed survey method and used anquette, interview, observation, and data documentation techniques. The research samples included 35 students of the sixth grade to join UASBN and the teachers of Indonesian language, math, and natural science. The findings show (a) the PAIKEM instruction strategy is implemented effectively, (b) the students’ scores in UASBN are categorized very good, and (c) there is a ppositive relationship between the instructional strategy and the scores in UASBN.